Political Issues of Presidential Candidates General Election 2024 In Indonesia Based On Social Media Research by Nodexl of Big Data From Twitter - Priyantomo, Bayu Aulia (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Two years before the presidential candidates general election 2024 in Indonesia. There are so many presidential candidates nominated by political parties that are discussed by netizens, especially through social media by Twitter using the keywords PILPRES 2024 and CAPRES 2024.This study uses big data analysis social media research to try to understand who the presidential candidate is in forming opinions, behaviors and issues discussed by netizens or presidential voters by NodeXL of big data from Twitter. Based on the results of the study, it shows that the issue of presidential candidates that are often discussed by Twitter users or netizens 7 large clusters have the opportunity to become 2024 presidential candidates Anis Baswedan, Puan Maharani, Ganjar Pranowo, Prabowo Subianto, Erick Thohir, and Gus Aos ( cleric who support Anis Baswedan to become the CAPRES 2024). Meanwhile, Muhaimin Iskandar, Ridwan Kamil, Mahfud MD, and Susi Pudjiastuti are less often talked about by social media users or netizens